2018
DOI: 10.1159/000488613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SIRT2 Alleviates Fibroblast Activation and Renal Tubulointerstitial Fibrosis via MDM2

Abstract: Background/Aims: Renal tubular epithelial cells and fibroblasts are the main sources of myofibroblasts, and these cells produce the extracellular matrix during tubulointerstitial fibrosis (TIF). Histone deacetylases (HDAC) inhibitors exert an antifibrogenic effect in the skin, liver and lung. Sirtuin 2 (SIRT2), which is a class III HDAC, is an important member of NAD+-dependent protein deacetylases. The current study evaluated the role of SIRT2 in renal TIF. Methods: Immunohistochemical staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…SIRT2 appears to promote fibroblast activation by enhancing TGF‐β1‐induced MDM2 expression, which leads to the subsequent inhibition of p53 (Figure ) . SIRT2 inhibition by genetic knockdown or pharmacological inhibitors has significantly reduced the fibroblast activation and suppressed the expression of MDM2 …”
Section: Roles Of Mdm2 In Kidney Diseases and Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…SIRT2 appears to promote fibroblast activation by enhancing TGF‐β1‐induced MDM2 expression, which leads to the subsequent inhibition of p53 (Figure ) . SIRT2 inhibition by genetic knockdown or pharmacological inhibitors has significantly reduced the fibroblast activation and suppressed the expression of MDM2 …”
Section: Roles Of Mdm2 In Kidney Diseases and Diabetesmentioning
confidence: 99%
“…Renal fibrosis (RF) is a common pathology of chronic kidney disease that is characterized by glomerulosclerosis and tubulointerstitial fibrosis (TIF) . He et al have found that SIRT2 is highly expressed in the tubulointerstitium from TIF patients and mice with unilateral ureteral obstruction, and SIRT2 plays an important role in activating fibroblasts and TIF. SIRT2 appears to promote fibroblast activation by enhancing TGF‐β1‐induced MDM2 expression, which leads to the subsequent inhibition of p53 (Figure ) .…”
Section: Roles Of Mdm2 In Kidney Diseases and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some scholars have found that the activation of Sirtuin 2(SIRT2) promotes fibroblast activation and aggravates renal fibrogenesis (Ponnusamy et al, 2015). As expected, its inhibitor suppresses fibroblast activation through murine double minute2(MDM2), suggesting the SIRT2-MDM2 signaling pathway may be a therapeutic target for renal tubulointerstitial fibrosis (He et al, 2018). In the study of ischemic renal fibrosis, Cyr61 may not only inhibit the fibrotic phenotype of fibroblasts, but also inhibit the proliferation of fibroblasts through the p53/P21/Rb pathway (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…SIRT1 and SIRT2 are found expressed in renal fibroblasts and tubular cell, while cellular distribution of other members in this subfamily is not clear. Studies have demonstrated the role of class III HDACs in tissue fibrosis, but results regarding SIRT1 in renal fibrosis are controversial, as both activation and inhibition of SIRT1 can attenuate renal fibrosis [25][26][27][28][29]. HDAC 11 is the sole member of class IV and is localized to the nucleus and may be involved in regulating the expression of interleukin 10.…”
Section: Hdacs In Mammalian Cellmentioning
confidence: 99%